Cough monitoring systems in adults with chronic respiratory diseases: a systematic review - Latisha E. Witjaksono; Max Schulte; Anne E. Holland; Marlies S. Wijsenbeek; Yet H. Khor (European Respiratory Review)
Background The role of objective cough monitoring systems for assessments in adults with chronic respiratory diseases (CRDs) is unclear. This systematic review aimed to synthesise current literature on frequency of use and characteristics of these systems. Methods MEDLINE, Embase and CENTRAL were systematically searched to identify relevant literature evaluating cough in adults with CRDs using objective cough monitoring systems. The primary outcomes were utility and characteristics of the systems, with the secondary outcome being usability. Results We identified 54 primary studies (4909 patients, with 3364 having idiopathic chronic cough). Included studies were generally of low risk of bias. Objective monitoring systems identified were VitaloJAK (n=19 studies), Leicester Cough Monitor (LCM, n=18), LEOSound (n=2), PulmoTrack (n=2), Hull Automated Cough Counter (HACC, n=1), LifeShirt (n=1), and unnamed devices (n=11). There was limited assessment against manual counting, with low-to-moderate correlation to patient-reported outcome measures for VitaloJAK (p<0.05), LCM (r=0.43–0.78) and unnamed devices (r=0.38–0.40). Test–retest consistency was evaluated in two studies, showing favourable results. There was at least moderate effect size of longitudinal measurement changes to various treatments for VitaloJAK (nine out of 16), LCM (two out of eight), HACC (n=1), LCM and HACC (n=1), PulmoTrack (n=1) and unnamed devices (n=3). Conclusions Few studies evaluated the agreement of objective cough monitoring systems against manual counting. Most studies were conducted in patients with idiopathic chronic cough, with the VitaloJAK and LCM being were the most evaluated objective cough monitoring systems. Further evaluation of objective cough monitoring systems is needed for research and clinic application.